Law Enforcement of Political Corruption as a Form of Abuse of Political Power - Yuliawan, Indra (Law Research Review Quarterly, 2018)
Artidjo Alkostar defines political corruption as corruption committed by public officials and the proceeds of crime are channeled for political activities, in other words, crime 'political corruption' is an act committed by public officials who hold political power but political power is used as a tool of crime. Law enforcement efforts against political corruption carried out by state officials have been regulated in the Corruption Criminal Act coupled with the existence of the Corruption Eradication Commission has become a milestone in the effort of Law Enforcement in Corruption Crimes. However, law enforcement efforts for political corruption are not easy because they are also influenced by the dominance of political parties in a number of state institutions, apart from legistalative institutions, the dominance of political parties also to financial institutions, ministries, and executive institutions as implementing policies. which is fierce can undermine law enforcement efforts on political corruption because there are certainly many interventions from political parties in government policy. The Role of Law Enforcement Officials such as the Police, Prosecutors' Office and the Judiciary as well as the Role of Advocates is a positive synergy in addition to the policies of the authorities to limit the role of Political Parties in government policies.